Pengembangan Media Ajar Melalui Web dalam Mendukung Pembelajaran Berbasis Teknologi - Fransiskus Markus Pereto Keraf; Leonard Peter Gelu; Kristoforus Fallo; Yanuarius Sani Feka; Yohanes Pebrian Vianney Mambur (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The priority problem experienced by partners or training participants is difficulty in using web-based technology to support technology-based learning at school and at home. The use of web technology such as WordPress access, cloud ID, and user com and its use in technology-based learning is not yet well known. The activity began with a focus group discussion to listen to teachers' statements about technology-based learning in the Kefamenanu 1 State Vocational School environment. After the FGD activities were carried out, it was continued with socialization regarding program introductions, technology-based learning materials, and introduction to the web. This section socializes technology-based learning models in general and the use of web media in particular. The web-based learning tool intended is the use of the Google site as a media data bank and learning tool. Based on the results of the implementation of service activities carried out with the service team at Kefamenanu 1 State Vocational School, various achievements were successfully achieved. This achievement is increasing partner empowerment through comparing descriptions of test results/knowledge scores before and after implementing activities.